Desert Spread a Quantitative Analysis in The Arid Zone of Rajasthan - Mann, H S; Malhotra, S P; Kalla, Jagdeesh C (Annals of Arid Zone, 2016)
In this study an attempt has been made lo examine quantitatively, the spread of desert through comparison of parameters like land-use. availability of water. and crop yield performances between desert area and bordering districts for more than 13 years, The results do not support the popular belief that the desert is on the march to engulf adjoining areas to the east of the desert.